The word nzĭ in Green Mong (Miao) - Lyman, Thomas Amis (2024)
In view of the current interest in Mong/Hmong studies. I am submitting my translational definition of the word nzĭ , a highly productive form in the Mong Njua (Green Mong) language. This form is an extremely difficult one to translate and the present rendering will, therefore, prove of considerable value to Tibeto-Burman Area specialists.